Genetic variations associated with response to dutasteride in the treatment of male subjects with androgenetic alopecia - Rhie, Arang; Son, Ho-Young; Kwak, Soo Jung; Lee, Seungbok; Kim, Dong Young; Lew, Bark-Lynn; Sim, Woo-Young; Seo, Jeong-Sun; Kwon, Ohsang; Kim, Jong-Il; Jo, Seong Jin (PloS one, 2019)
Dutasteride, a dual inhibitor of both type I and II 5α-reductases, is used to treat male pattern hair loss (MPHL). However, patient response to dutasteride varies in each individual, the cause of which is yet to be identified. To identify genetic variants associated with response to dutasteride treatment for MPHL, a total of 42 men with moderate MPHL who had been treated with dutasteride for 6 months were genotyped and analysed by quantitative linear regression, case-control association tests, and Fisher's exact test. The synonymous single nucleotide polymorphism (SNP) rs72623193 in DHRS9 was most significantly associated with response to dutasteride, followed by the non-synonymous SNP rs2241057 in CYP26B1. Additionally, variants in ESR1, SRD5A1, CYP19A1, and RXRG are suggested to be associated with response to dutasteride. Cumulative effect and interaction among these SNPs were presented in both additive and non-additive models.